A new species of Near-shore Marine Goby (Pisces: Gobiidae: Nesogobius) from Kangaroo Island, Australia - Hammer, Michael P.; Hoese, Douglass F.; Bertozzi, Terry (Zootaxa, 2015)
Nesogobius is one of two goby genera with all species wholly restricted to temperate Australian waters. Described here is a new member of the genus discovered during near-shore marine and estuarine fish sampling along the central southern Australian coastline. The tiger sandgoby Nesogobius tigrinus sp. nov. is distinguished from other congeners by a combination of colouration including four prominent vertical black bars on males; morphological characters involving body scales (large), head scales (naked), body depth (slender) and gill opening (wide); meristic counts including a lack of second dorsal and anal fin spines; and mitochondrial DNA sequence divergence. The species appears to be a narrow range endemic, restricted to specific sub-tidal habitat in the unique sheltered embayments of northeast Kangaroo Island. This study forms part of ongoing investigations to more fully describe the biodiversity and conservation requirements of the regional ichthyofauna.